Requirements for a hybrid TPM based on optimized ML-DSA post-quantum signature - Rampazzo, Felipe José Aguiar; Meneses, Rodrigo de; Teixeira, Caio; Henriques, Marco A. Amaral (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2024)
A Trusted Platform Module (TPM) is used to ensure trust between connected devices by storing device integrity measurements. Both TPM and traditional security systems rely on asymmetric cryptography, which can be vulnerable to quantum computers. This work aims to find the requirements for a TPM secured by traditional and post-quantum algorithms, considering the transition through a hybrid model that remains secure even if the post-quantum algorithm breaks. Then, it analyzes the impact of this hybrid model in a TPM using a hybrid TPM emulated in software.